Changes in the rat urinary bladder after the relief of outflow obstruction – tracing targets for treatment of persistent symptoms in patients - Andersson, Karl-Erik; Uvelius, Bengt (Frontiers in Urology, 2022)
Studies on patients with bladder outflow obstruction who have undergone surgery for benign prostatic hyperplasia, successfully relieving the obstruction, have revealed a persistence of storage symptoms associated with detrusor overactivity (DO) in 20% to 40 % of patients. To study the underlying mechanisms, we have used a common rat model of obstruction/de-obstruction, assuming that non-voiding contractions can be used as a surrogate parameter for DO in humans. Using microarray analysis and electron microscopic images from obstructed and de-obstructed bladder tissue we have tried to identify changes that could serve as a basis for the search of new targets for drugs. Even if voiding function is rapidly normalized after release of outflow obstruction and many of the morphological changes are reversed, the microarray analysis revealed that the de-obstructed rat bladder has gene expressions, structural, and functional properties that make it distinctly different from both control and obstructed bladders. We suggest that whole bladder arrays can be used for identifying cellular mechanisms that could be targets for drugs meant for treatment of persistent DO and LUTS after de-obstruction. Based on available array information for some membrane receptors and morphologic structures with corresponding changes in bladder function, it seems worthwhile to re-assess the development potential for e.g., endothelin receptor antagonists, purinergic receptor antagonists and Rho-kinase inhibitors.